Endogenous segregation dynamics and housing market interactions: An ABM approach - Said Benjamin Bonakdar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
In contrast to previous research, I hypothesize that residential segregation patterns do not only result from an individual's perception of different ethnicities, but is rather affected by housing market interactions and socioeconomic endowment, like income and education. I implement a theoretical agent-based model, which contains three main features: agents' socioeconomic endowment, the quantification of one's Willingness-to-Stay within a neighborhood and housing market interactions if an agent decides to move. The results indicate that housing market interactions, the valuation of socioeconomic factors, but also the increasing share of minority groups diminish the absolute level of racial segregation. The analysis shows that house price clusters dominate urban areas, since individuals have an incentive to stay in more expensive neighborhoods in which they made a bargain. An increase in house price segregation can be observed if individuals strongly undervalue their own house and if individuals have higher access to credit. I can show that these market interactions lead to lock-in effects for low-income individuals, since they lack the necessary budget and suffer under negative equity. Thus, residential segregation shows a strong dependency on housing market interactions and is more complex than presumed by Schelling's Spatial Model or the White Flight Hypothesis. – – Diesem Paper unterliegt die Hypothese, dass Segregationsmuster nicht nur das Resultat von individueller Wahrnehmung bezüglich der Anzahl direkter Nachbarn mit anderer ethnischen Zugehörigkeit sind, sondern vor allem durch Häusermarktinteraktionen sowie individuellen Unterschieden in Einkommen und Bildungsständen getrieben werden. Hierzu wird ein theoretisches agenten-basiertes Simulationsmodell entwickelt, dass sich durch explizit drei Merkmale auszeichnet: die Zuweisung heterogener sozioökonomischer Charakteristika, die Quantifizierung der sogenannten Willingness-to-Stay eines Individuums innerhalb einer Nachbarschaft und die Interaktion auf dem Häusermarkt, sobald ein Agent die Umzugsentscheidung trifft. Die Ergebnisse zeigen, dass die Häusermarktinteraktionen, die Bewertung der sozioökonomischen Merkmale und ein wachsender Anteil von Minderheiten innerhalb der Bevölkerung das absolute Maß an ethnischer Segregation senkt. Die Analyse verdeutlicht, dass Hauspreiscluster die urbane Region dominieren, da Individuen einen Anreiz haben in reicheren Nachbarschaften zu verweilen, sofern sie einen relativ günstigen Kaufpreis aushandeln konnten. Die Hauspreissegregation steigt, sofern eine hohe Unterbewertung des eigenen Hauses festzustellen ist und zugleich ein höherer Kreditzugang vorliegt. Zudem führen die Marktinteraktionen zu Lock-In Effekten für die untere Einkommensklasse. Besonders diese Individuen leiden unter Negative Equity, bei dem Häuser zu höheren Preis gekauft worden sind, als sie anschließend bewertet werden. Folglich weist Segregation eine starke Abhängigkeit von Häusermarktinteraktionen auf und ist ein komplexeres Phänomen als ursprünglich von Schelling oder der White Flight Hypothesis angenommen.
Keywords: C63; R21; R23; 330; agent-based modelling; residential choice; housing demand; neighborhood characteristics; segregation